A four-layer Ag-ZnO-LPFG structure for improving temperature sensitivity and coupled-wavelength transmittance stability. (30th November 2020) - Wang, Jin; Wang, Li; Su, Xueqiong; Pan, Yong; Gao, Dongwen; Cheng, Peng; Yan, Huanhuan
Abstract: A novel long-period fiber grating (LPFG) with a four-layer structure is proposed, made by coating double layers of both ZnO and Ag onto a bare LPFG. Pulsed laser deposition (PLD) technology can effectively control the flatness and nanoscale thickness of ZnO film, which is conducive to achieving full energy coupling with the Ag layer and the grating. Compared with SiO2, ZnO has a higher thermal expansion coefficient and refractive index, which ensures that coated LPFG has a higher temperature sensitivity. As the fourth layer of the structure, colloidal silver is coated onto the surface of the ZnO film at an optimal thickness by a spin-coating method. The higher thermal expansion coefficient of the Ag film and a plasma resonance effect on its surface cause the temperature sensitivity to increase again. The sensitivity of the coated Ag-ZnO-LPFG structure is 1.4 times higher than that of the bare fiber. The temperature sensitivity is increased from 0.063 nm °C −1 to 0.088 nm °C −1, while retaining good linearity. We also solve the problem whereby the coating disturbs the coupled-wavelength transmittance, and by doing so, we increase the stability of the coupled-wavelength transmittance and enhance measurement accuracy.